2017
DOI: 10.1002/jhet.2979
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel [1,2,4]Triazolo[1,5‐c]quinazoline Derivatives as Antibacterial Agents

Abstract: A series of new 2‐aryl‐5‐methyl‐[1,2,4]triazolo[1,5‐c]quinazoline derivatives (5a–5g) have been synthesized by the reaction of 3‐amino‐2‐methylquinazolin‐4‐(3H)‐one (3) with aromatic nitriles in potassium tert‐butoxide under reflux conditions. 3‐Amino‐2‐methylquinazolin‐4‐(3H)‐one (3) was synthesized by the reaction 2‐methyl‐4H‐benzo[d][1,3]oxazin‐4‐one (2) with hydrazine hydrate. The chemical structure of products was confirmed by IR, 1H, 13C NMR and elemental analysis. These compounds were screened for antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 34 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Recent studies show that the biological properties of compounds are increasing from year to year. It was shown that various derivatives of 1,2,4-triazoles possessed antimicrobial [Koparir M et al, 2013], antitumor [Li YH et al, 2017;Zhang G, Hu Y, 2007], antibacterial [Gao F et al, 2019;Karnik А et al, 2006;Arafa W, 2010;Puthiyapurayil P et al, 2011;Zeydi M et al, 2017], fungicidal [Jian F et al, 2006;Song HX, Shi DQ, 2014] activities. For the first time it has been found that at a certain set of substituents in a molecule, the triazole derivatives show affinity for the human adenosine A3 receptor [Federico S et al, 2018] and exhibit insecticidal properties against T cinnabarinus [Luo Y et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that the biological properties of compounds are increasing from year to year. It was shown that various derivatives of 1,2,4-triazoles possessed antimicrobial [Koparir M et al, 2013], antitumor [Li YH et al, 2017;Zhang G, Hu Y, 2007], antibacterial [Gao F et al, 2019;Karnik А et al, 2006;Arafa W, 2010;Puthiyapurayil P et al, 2011;Zeydi M et al, 2017], fungicidal [Jian F et al, 2006;Song HX, Shi DQ, 2014] activities. For the first time it has been found that at a certain set of substituents in a molecule, the triazole derivatives show affinity for the human adenosine A3 receptor [Federico S et al, 2018] and exhibit insecticidal properties against T cinnabarinus [Luo Y et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Moreover, cyclisation of above-mentioned hydrazides yielded substituted triazolo [c]quinazolines that show a wide range of biological activity including anticonvulsant, antitumor, hypoglycemic, antibacterial and other activities. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Despite the numerous publications devoted to the chemistry and biology of hydrazides formed by quinazolin-4(3H)-ylidenehydrazine, some features of their formation, reactivity, physicochemical and biological properties have been insufficiently studied. One of the promising directions of studies is the synthesis and further cyclization of hydrazides formed by quinazolin-4(3H)-ylidenehydrazine and dicarboxylic acids or their monoesters.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the literature data shows that the intensity of research in this area is likely to increase, revealing new useful properties, expanding the existing wide range of biological effects of 1,2,4‐triazole derivatives. Recent studies have found that new representatives of this series revealed antimicrobial, antibacterial,– anti‐fungal, anticonvulsant,– antitumor,– antioxidant, activities, specific activity against influenza A/H1 N1, growth‐stimulating, herbicidal, insecticidal, anti‐tuberculosis, anticholinesterase activities. They inhibit the interaction of annexin A2 and protein S100 A10, HIV 1 replication, p38 MAР kinase, HDAC‐tabulin,– adenosine receptor antagonists, agents in the treatment of Alzheimer's disease, ion channel modulators, etc.…”
Section: Introductionmentioning
confidence: 99%